2000
DOI: 10.1002/(sici)1521-3862(200006)6:3<109::aid-cvde109>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Electrical Properties and the Morphology of Low-Pressure MOCVD Titanium Oxynitride Thin Films Grown at Various Temperatures

Abstract: Titanium oxynitride (TiN x O y ) thin films were deposited by low-pressure metal±organic CVD (LP-MOCVD) on (100) silicon, sapphire, and polycrystalline alumina substrates. Titanium isopropoxide (TIP) and ammonia were used as precursors. The influence of the growth temperature, ranking from 450 C to 750 C, was investigated by scanning electron microscopy (SEM), and electrical DC measurements. Rutherford back-scattering (RBS) measurements were used to determine the N/O ratio in the films. The surface observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
(17 reference statements)
2
17
0
1
Order By: Relevance
“…The (1 0 0) GaAs substrates were heat-treated in a MOCVD system yet described [12]. The process was carried out under flows of NH 3 ; titanium isopropoxide (TiP) OM precursor and N 2 which was used as carrier gas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (1 0 0) GaAs substrates were heat-treated in a MOCVD system yet described [12]. The process was carried out under flows of NH 3 ; titanium isopropoxide (TiP) OM precursor and N 2 which was used as carrier gas.…”
Section: Methodsmentioning
confidence: 99%
“…Typical flow rates were: 0.5 slm of N 2 through the TiP held at 40 C, 0.5 slm of NH 3 and 1 slm of N 2 total carrier gas flow rate. Previous works have shown that TiP is a titanium and oxygen precursor for the MOCVD growth of TiO 2 [13] and TiN x O y [12] films. Prior to their introduction in the CVD reactor, GaAs (1 0 0) substrates were conventionally cleaned (H 2 SO 4 : H 2 O 2 : H 2 O, 6:1:1) and N 2 blow-dried.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous papers have been published on deposition of thin films of nitrogen-doped TiO 2 or oxygen-doped TiN [21][22][23][24][25][26][27]. The most efficient methods of deposition seem to be LP-MOCVD (lowpressure metal organic chemical vacuum deposition) [21][22][23][24] and reactive magnetron sputtering [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…The most efficient methods of deposition seem to be LP-MOCVD (lowpressure metal organic chemical vacuum deposition) [21][22][23][24] and reactive magnetron sputtering [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…[8] In particular, the application of nitrogen-doped titania as photocatalyst has received increasing attention over the last years because N-doping is found to be particularly effective in decreasing the bandgap of anatase. The incorporation of nitrogen into the titania network has been achieved trough different methods, such as reactive DC magnetron sputtering, [9] ionbeam-assisted deposition, [10] position, [11] laser ablation, [12] or ball milling, [13] using a variety of nitrogen sources, such as amines, urea, N 2 , or ammonia, [14][15][16][17] and different titanium sources, such as TiCl 4 , [18] TiCl 3 , [19] Ti(OH) 4 , [20] or Ti(SO 4 ) 2 . [21] However, it should be pointed out that the visible-light photocatalytic activity of the resulting materials is highly sensitive to the synthetic route used in their preparation.…”
Section: Introductionmentioning
confidence: 99%